Controlling the Fiscal Costs of Banking Crises - Honohan, Patrick; Klingebiel, Daniela (World Bank, Washington, DC, 2014)
In recent decades, a majority of countries have experienced a systemic banking crisis requiring a major-and expensive-overhaul of their banking system. Not only do banking crises hit the budget with outlays that must be absorbed by higher taxes (or spending cuts), but they are costly in terms of forgone economic output. Many different policy recommendations have been made for limiting the cost of crises, but there has been little systematic effort to see which recommendations work in practice. The authors try to quantify the extent to which fiscal outlays incurred in resolving banking distress can be attributed to crisis management measures of a particular kind adopted by the government in the early years of the crisis. They find evidence that certain crisis management strategies appear to add greatly to fiscal costs: unlimited deposit guarantees, open-ended liquidity support, repeated recapitalization, debtor bail-outs, and regulatory forbearance. Their findings clearly tilt the balance in favor of a strict rather than an accommodating approach to crisis resolution. At the very least, regulatory authorities who choose an accommodating or gradualist approach to an emerging crisis must be sure they have some other way to control risk-taking.